Transcriptomic Changes in Hot Spring Frog Tadpoles (Buergeria otai) in Response to Heat Stress - Komaki, Shohei; Matsunami, Masatoshi; Lin, Jhan-Wei; Lee, Ko-Huan; Lin, Yen-Po; Lee, Yu; Lin, Si-Min; Igawa, Takeshi (Frontiers in Ecology and Evolution, 2021)
Buergeria frog tadpoles exhibit high thermal tolerance and are occasionally found in water pools that temporarily exceed 40 °C. With the aim of understanding how they can cope with the severe heat stress, we performed RNA-seq of three heat-treated (38 °C) and three control (25 °C) tadpoles and compared their transcriptomic profiles. We identified 382 differentially expressed transcripts. A protein-protein interaction network analysis of these transcripts further identified hub proteins involved in protein degradation, stress granule assembly, and global suppression of DNA transcription and mRNA translation. Along with the avoidance behavior against high water temperature, these endurance mechanisms potentially support tadpoles to survive in high temperatures for short periods of time. Similar mechanisms may exist in many other amphibian species whose habitats are prone to high temperatures.